Corporate governance, financing and gender: A study of SMEs from Argentinean Securities Markets - Briozzo, Anahi Eugenia (2017)
The objective of this work is to study corporate governance (CG) and the financing of small and medium sized enterprises (SMEs) from a gender perspective. Particularly, the participation of women in the holding, administration (board of directors and senior management), and external audit of the SMEs that participate in the Argentinian stock markets is analyzed. The results show that there are significant relations between the participation of women in ownership, external audits, and financing decisions. However, no relation is found between the participation of women at the different levels of the CG.